If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(4q + 2) = -3q + 10 Reorder the terms: -5(2 + 4q) = -3q + 10 (2 * -5 + 4q * -5) = -3q + 10 (-10 + -20q) = -3q + 10 Reorder the terms: -10 + -20q = 10 + -3q Solving -10 + -20q = 10 + -3q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '3q' to each side of the equation. -10 + -20q + 3q = 10 + -3q + 3q Combine like terms: -20q + 3q = -17q -10 + -17q = 10 + -3q + 3q Combine like terms: -3q + 3q = 0 -10 + -17q = 10 + 0 -10 + -17q = 10 Add '10' to each side of the equation. -10 + 10 + -17q = 10 + 10 Combine like terms: -10 + 10 = 0 0 + -17q = 10 + 10 -17q = 10 + 10 Combine like terms: 10 + 10 = 20 -17q = 20 Divide each side by '-17'. q = -1.176470588 Simplifying q = -1.176470588
| r=-20+10a | | -3*-8-9= | | 3=4(x+3)-5 | | -79+12x=38+3x | | 9y-9=9y-y | | 44-3x=15x+16 | | 2(5-4)= | | (2-5)= | | 7*-2+3= | | 0.08x+0.07(15000-x)=1110 | | 2k+h=1 | | -3x-4(-0.5+-0.75)=2 | | 5*3+4= | | -32+9x=8+5x | | X-8=2x+9 | | -2x^3(3x^2-6x-1)= | | -7z-49=2-6z | | -3(-2.6-1)+5=2(-2.6+1)-3(-13-1)+13 | | -29+x=-7x+51 | | h+2k=14k | | 3.4x-4.6=2.2 | | -46+2x=30+6x | | 12k=1-2k | | 6m-5=7m+5-m | | 19-h-h=-18 | | 7-(9x+3)=-9x-4 | | x(7+66)= | | y=2-5+-2.5 | | 7-x+4=27 | | x^8-24x^4+128=0 | | 4x*2+9x+22=0 | | 75=(3-6n-5) |